MENGEJAR PERINGKAT HDI*) NEGARA-NEGARA DI LINGKUNGAN ASEAN: Bechmarking Indonesia dan Vietnam - Suryadi, Ace (Journal of Indonesian Economy and Business, 2008)
This article is to aim at scrutinizing factors that have explained the extent to whichÂ magnitude and rank of the Human Development Index of Indonesia had or had not improved in theÂ last 8 year. Within this period, the Indonesiaâs HDI has been consistently ranked at the 7th positionÂ after Vietnamâs, and Indonesia has won the race with this country only in 2004 and 2006.Nevertheless, Indonesia has a great potential to manage some measurable improvement throughÂ learning from other ASEAN countriesâ experiences. Vietnam is the immediate choice for IndonesiaÂ to benchmark for the future HDI improvement. In the HDI 2007, Indonesia is already in favor inÂ three out of the four indicators used to constitute the composite HDI, such as Literacy, CombineÂ GER, and GDP per-capita, whereas Vietnam only is in the life expectancy. In the absence ofÂ weighting in the process of compositing the index, Indonesia has to accept the fact that its HDI isÂ lower than that of Vietnam. In the future Indonesia needs being well organized and betterÂ coordination in managing HDI improvement affairs to make sure that the right data are timelyÂ collected and reported and the better policies on human development are implemented for moreÂ Jurnal Ekonomi dan Bisnis Indonesia, Vol 23 No.1,Januari 2008Â effective human development programs.Keywords: Angka Harapan Hidup, Angka Melek Aksara, Human Capital, Human DevelopmentÂ Index, Manpower Requirement Approach, Partsipasi Pendidikan, Pendapatan Perkapita,Â Rights Base Approach.